LEVELS OF HORMONES, microRNA AND CYTOKINES IN LYMPH FROM HEALTHY AND EXPERIMENTAL BREAST CANCER - A. P. Lykov; A. V. Kabakov; N. A. Bondarenko; O. V. Poveshchenko; T. V. Raiter; O. V. Kazakov; D. N. Strunkin; A. F. Poveshchenko; N. B. Orlov; V. I. Konenkov (Сибирский онкологический журнал)
The involvement of hormones, microRNAs and cytokines in breast cancer pathogenesis has been well established. Lymph picks up secretory products of breast cancer cells. The purpose of the study was to evaluate the levels of hormones, microRNAs and cytokines in lymph. Wistar rats were injected with N-methyl-N-nitrosourea to induce breast cancer. The rats were subjected to either surgery alone or chemotherapy alone (cyclophosphamide, methotrexate and 5-fluorouracil). In some animals, surgery was followed by chemotherapy. The levels of follicle-stimulating hormone (FSH), prolactin, luteinizing hormone (LH), estradiol (E2) and thyroglobulin (TG), microRNA-21, microRNA-221, microRNA-222, microRNA-429 and 24 cytokines were determined. Chemotherapy was shown to result in the reduction in the levels of prolactin, thyroglobulin, FSH and estradiol. In rats with breast cancer, the expression levels of microRNA-21, microRNA-221 and microRNA-222 were increased, and the expression levels of microRNA-429 were decreased. In breast cancer rats, the levels of most cytokines were found to be increased. Correlations between the levels of cytokines, hormones, and microRNAs in lymph were identified. Differences in the expression levels of cytokines, hormones, and microRNAs in lymph with respect to treatment option were detected.